2017
DOI: 10.7567/jjap.56.110303
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of epitaxial yttrium–iron garnet micropatterns using metal–organic decomposition with electron-beam irradiation

Abstract: We have succeeded in obtaining epitaxial yttrium–iron garnet (YIG) micropatterns on a gadolinium-gallium garnet (GGG) substrate by a metal–organic decomposition method with electron-beam (EB) irradiation. We have demonstrated that metal-octylates of Y and Fe showed negative exposure behavior for EB irradiation. X-ray diffraction measurements indicated that the YIG micropatterns were epitaxially well grown on a GGG(111) substrate. The magnetization curve of the YIG micropatterns showed a clear hysteresis loop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Quite recently, we have succeeded in fabricating high-quality epitaxial YIG micropatterns on a GGG substrate using the EB-MOD method. 30) These YIG micropatterns had good crystallographic and magnetic properties similar to epitaxial YIG films by a conventional MOD method. Since YIG is one of the fundamental RIGs, we expect that this technique can be applied to other RIG materials.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Quite recently, we have succeeded in fabricating high-quality epitaxial YIG micropatterns on a GGG substrate using the EB-MOD method. 30) These YIG micropatterns had good crystallographic and magnetic properties similar to epitaxial YIG films by a conventional MOD method. Since YIG is one of the fundamental RIGs, we expect that this technique can be applied to other RIG materials.…”
mentioning
confidence: 91%
“…The EB sensitivity of the MOD solution for Bi:YIG was 1.13 × 10 4 μC cm −2 , which was determined by the electron-dose dependence of the remaining-film thickness for the precursor film (not shown), and it was similar to one for YIG. 30) After the EB irradiation, the antistatic agent film was removed with DIwater and the precursor film was developed with toluene. Finally, the patterned films were annealed at 750 °C in air for 3 h. We confirmed that the obtained Bi:YIG patterns were epitaxially grown on an GGG(111) substrate using X-ray diffraction measurements under out-of-plane and in-plane configuration.…”
mentioning
confidence: 99%